A Radio-interferometric Imaging Method Based on the Wavelet Tight Frame - Xiaocheng Yang; Xiang You; Lin Wu; Jingye Yan; Feng Liu; Mingfeng Jiang; Junbao Zheng (The Astronomical Journal)
Reconstructing the signal from measured visibilities in radio interferometry is an ill-posed inverse problem. In this paper, we present a novel radio-interferometric imaging method based on the wavelet tight frame aimed at efficiently obtaining an accurate solution. In our approach, the signal is sparsely represented by the directional tensor product complex tight framelets, which can effectively capture the texture and shape features of the images. To enhance computational efficiency, we employ the projected fast iterative soft-thresholding algorithm for solving the l _1 -norm minimization problem. Several simulation experiments are carried out to verify the effectiveness and performance of the proposed method.